Educational Video Improves Knowledge about Outpatients' Usage of Antibiotics in Two Public Hospitals in Indonesia - Fauna Herawati; Rika Yulia; Bustanul Arifin; Ikhwan Frasetyo; Setiasih; Herman J. Woerdenbag; Christina Avanti; Retnosari Andrajati (MDPI AG, 2021)
The inappropriate use or misuse of antibiotics, particularly by outpatients, increases antibiotic resistance. A lack of public knowledge about "Responsible use of antibiotics" and "How to obtain antibiotics" is a major cause of this. This study aimed to assess the effectiveness of an educational video about antibiotics and antibiotic use to increase outpatients' knowledge shown in two public hospitals in East Java, Indonesia. A quasi-experimental research setting was used with a one-group pre-test-post-test design, carried out from November 2018 to January 2019. The study population consisted of outpatients to whom antibiotics were prescribed. Participants were selected using a purposive sampling technique; 98 outpatients at MZ General Hospital in the S regency and 96 at SG General Hospital in the L regency were included. A questionnaire was used to measure the respondents' knowledge, and consisted of five domains, i.e., the definition of infections and antibiotics, obtaining the antibiotics, directions for use, storage instructions, and antibiotic resistance. The knowledge test score was the total score of the Guttman scale (a dichotomous "yes" or "no" answer). To determine the significance of the difference in knowledge before and after providing the educational video and in the knowledge score between hospitals, the (paired) Student's t-test was applied. The educational videos significantly improved outpatients' knowledge, which increased by 41% in MZ General Hospital, and by 42% in SG General Hospital. It was concluded that an educational video provides a useful method to improve the knowledge of the outpatients regarding antibiotics.